Socialization Of Prevention and Management Of Covid-19 Cianjur District Goverment - Warno, Warno (International Journal of Educational Research & Social Sciences, 2021)
The development of the spread of Covid-19 in Cianjur Regency has spread, as many as seven sub-districts in Cianjur Regency have the highest number of confirmed positive cases of Covid-19 compared to others, averaging over 100 cases. The seven sub-districts include Cianjur, Cipanas, Pacet, Sukaresmi, Cugenang, Karangtengah and Ciranjang districts. Based on this case, the Cianjur Regency Government conducted outreach on prevention and control of COvid-19 in Cianjur. The purpose of this research is to know the analysis, strategy, mobilization, evaluation of the continuity of the socialization of the Covid-19 prevention and control program of the Cianjur Regency Government. This research method uses a qualitative approach with literature study analysis techniques in the scientific field of public policy. Meanwhile, the model used as a reference is the Advocacy Model. This model was first introduced by the Johns Hopkins University-USA Center for Communication Programs (CCP) in 1988. The results and discussion of this study were viewed from the aspect of data analysis in the field that the number of confirmed positive patients in Cianjur Regency was 316 people. In connection with this field analysis, organizations also need to be involved. The organizations involved are: Cianjur Health Office, Cianjur Police, community leaders, entrepreneurs, media, restaurant owners, RT and RW / Kampung, Alim ulama; Health cadres and Posyandu cadres, academics; Community, Stakeholders. Furthermore, the strategic aspect plays an important role, namely, the Cianjur Regency Government, West Java, continues to strive to prevent the spread of the corona virus or Covid-19, one of which is by imposing local isolation. For the third phase, namely Mobilization, which is carried out by the Cianjur Regency Government is very massive, namely implementing health protocols is still a mainstay in Cianjur Regency, West Java to prevent the spread of Covid-19, which has a very dynamic movement rate. The socialization was carried out by intensifying the 3M campaign to the community, namely wearing masks, washing hands, and maintaining distance in various activities. The stages of the action were carried out by the Cianjur Regency Government in collaboration with all parties. Not only the government, but also all other competent policy makers. 3M's Echo activity is a campaign to make people aware of the discipline of applying health protocols. This Echo socialization activity has the theme "Heup cicing covid (stop covid)." The evaluation stage, carried out by the Cianjur Regency Government, is that the old criteria noted that from 1-5 houses there were positive COVID-19 status were still yellow, while the new criteria stated that five or more houses were categorized. in the red zone, so that in Cianjur there are 67 RTs that enter the red zone. The Cianjur Regency Government has carried out continuity steps, namely monitoring the post in order for Cianjur residents to be sterile and monitoring to reduce the impact of Covid19. The government continues to carry out socialization of New Habit Adaptation.